What is the role of prognostic indexes in COVID-19 patients with diabetes mellitus? Data of patients from Turkey - Balin, Safak O.; Kazanci, Ulku; Demirdag, Kutbeddin; Akbulut, Ayhan (Future Medicine Ltd, 2022)
Aim: We aimed to determine the prognostic performance of the Glasgow Prognostic Score (GPS), systemic immune-inflammation index and early warning score (the 'ANDC' system) in patients with diabetes mellitus who had COVID-19. Patients & methods: Patients were divided into two groups: with and without diabetes mellitus. Results: In the diabetic patient group, the rates of in-hospital mortality, intensive care unit hospitalization and corticosteroid treatment were higher compared with the nondiabetic patient group (p < 0.05). A GPS of 2 was useful for predicting in-hospital mortality in diabetic patients (p < 0.05). The ANDC score was significantly higher in diabetic patients (p < 0.05) and in diabetic patients with mortality and those who needed ICU hospitalization (p < 0.05). Conclusion: The presence of a GPS of 2 at the time of admission and a high ANDC value were associated with poor prognosis in diabetic COVID-19 patients.
Keywords: COVID-19; diabetes mellitus; early warning score; Glasgow prognostic score; systemic immune-inflammation index